Kepemimpinan Ketua Yayasan Berdasarkan Kecerdasan Emosional (Eq) Di Ma’had Abdullah Bin Mas’ud Lita’hiil Huffadz - Subang - Aris Munandar (UNISAN JURNAL, 2024)
Abstract This research is qualitative research that describes the leadership of the Chairman of the Ma’had Abdullah Bin Mas’ud Lita’hiil Huffadz Educational Institution and analyzes the emotional intelligence perspective. This research was carried out using observation, interviews and documentation techniques. Testing the validity of the data uses triangulation techniques, which in this research emphasizes the source of the triangulation technique. The source is all citizens from the foundation of a good council, the environment, the people around them. This source will contain leadership data from the chairman of the Ma’had Abdullah Bin Mas’ud Lita’hiil Huffadz Foundation based on emotional intelligence. The research results show that the chairman of the Ma’had Abdullah Bin Mas’ud Lita’hiil Huffadz foundation has good leadership from an emotional intelligence perspective. The results of the analysis show that the chairman of the foundation carries out primal leadership very well. This is proven by triangulation of data and sources. The Chairman of the Daarul Ma’rifat Educational Institution, North Lampung, has a high commitment to the vision of the future, especially in times of stress or in the midst of increasing responsibilities. The chairman of the foundation takes an emotional approach to all citizens in the foundation. Foundation Chairs can read their own emotions and recognize their impact using instinct to guide decisions, know their strengths and limitations, can control emotions and demonstrate honesty and integrity, trustworthiness. The Chairman of the Foundation has good self-awareness and self-management, good social awareness and good relationship management. Keywords: Leadership, Foundation Chair, Emotional Intelligence